KOMBINASI DAN KOMPOSISI BAHAN BAKU UNTUK PENINGKATAN KUALITAS PAVING RUMPUT DI CV. X SURABAYA - Soejanto, Irwan (JURNAL TEKMAPRO, 2006)
As a product, grass paving has its own characteristic. The producers always try to keep the quality of their product to satisfy their consumers. This research tries to identify some factors that determine pressure strength of grass paving and some dominant factors generate optimum pressure strength and to recommend the ideal material composition to produce a good grass paving. The research shows portland cement composition (A), water (B), sand (C), and ash (D) determine the pressure strength of grass paving. The combination level factor: 2.7 kg portland cement , 0.9 lt water , 1.0 kg sand , and 2.0 kg ash generate optimum pressure strength of grass paving. The SN ratio is derived from 2.7 kg portland cement , 0.9 lt water , interaction between 2.7 kg portland cement with 1.4 kg sand , and interaction between 2.7 kg portland cement with 1.0 kg sand. Keywords: Taguchi method, pressure strength, grass paving.